Gone with the Headwinds : Global Productivity. (Staff Discussion Notes; Staff Discussion Notes ;, 2017)
Productivity growth-the key driver of living standards-fell sharply following the global financial crisis and has remained sluggish since, adding to a slowdown already in train before. Building on new research, this note finds that the productivity slowdown reflects both crisis legacies and structural headwinds. In advanced economies, the global financial crisis has led to 'productivity hysteresis'-persistent productivity losses from a seemingly temporary shock. Behind this are balance sheet vulnerabilities, protracted weak demand and elevated uncertainty, which jointly triggered an adverse feedback loop of weak investment, weak productivity and bleak income prospects. Structural headwinds-already blowing before the crisis-include a waning ICT boom and slowing technology diffusion, partly reflecting an aging workforce, slowing global trade and weaker human capital accumulation. Reviving productivity growth requires addressing remaining crisis legacies in the short run while pressing ahead with structural reforms to tackle longer-term headwinds.